2021
DOI: 10.3390/w13030264
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Microplastics in the Food Web of the Largest High-Elevation Lake in North America

Abstract: Microplastics have been documented in aquatic and terrestrial ecosystems throughout the world. However, few studies have investigated microplastics in freshwater fish diets. In this study, water samples and three trophic levels of a freshwater food web were investigated for microplastic presence: amphipods (Gammarus lacustris), Yellowstone cutthroat trout (Oncorhynchus clarkii bouvieri), and lake trout (Salvelinus namaycush). Microplastics and other anthropogenic materials were documented in water samples, amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
10
0
2
Order By: Relevance
“…Lower microplastic concentrations were also obtained in Yellowstone Lake in North America (2-11 MPs overall). Sampling was performed using a plankton net (Wildco ® mesh size 80 µm, diameter 20.32 cm, net material Nitex ® nylon), and samples were analyzed using FTIR and Raman spectroscopy [51]. Therefore, comparing our data on microplastic concentrations in lake waters with results obtained with similar methods showed a high consistency.…”
Section: Abundance and Distribution Of The Microplasticmentioning
confidence: 83%
“…Lower microplastic concentrations were also obtained in Yellowstone Lake in North America (2-11 MPs overall). Sampling was performed using a plankton net (Wildco ® mesh size 80 µm, diameter 20.32 cm, net material Nitex ® nylon), and samples were analyzed using FTIR and Raman spectroscopy [51]. Therefore, comparing our data on microplastic concentrations in lake waters with results obtained with similar methods showed a high consistency.…”
Section: Abundance and Distribution Of The Microplasticmentioning
confidence: 83%
“…In another study, 11 arthropod orders (Asellidae, Gammasidae, Astacidea, Tubi cidae, Erpobdellidae, Calopterygidae, Chironomidae, Sisalidae, Coenagrionidae, Ephemeroptera and Sigara) were tested for MPs and 86% of the individuals had MPs in their body and the size distribution of MPs in organisms and sediments were same while the number of MPs in every species varied greatly suggesting the taxon speci c uptake by the organism (Pan et al 2021). Driscoll et al, 2021 also investigated the presence of MPs in 32 individuals of Gammarus lacustris and observed the presence of MP in only single individual (Driscoll et al 2021). The largest study was carried out on 2772 individuals from 33 taxa, among which 48.5% organism had MPs in their body, the highest numbers of MPs were reported in the collector-gatherers and predators (Bertoli et al 2022) In mollusks, highest numbers of MPs were found in Anadara granosa which was 180.6 ± 21.22 MPs per individual in which bers were the most dominant type of MPs followed by fragments and lms (Fitri &Patria 2019).…”
Section: Interaction Of Mps With Invertebratesmentioning
confidence: 99%
“…Degradation means that microplastics have been exposed to various conditions for a long time, leading to their morphology and characteristics being altered to a certain extent [ 82 ], including photodegradation, mechanical degradation, thermal degradation and biodegradation [ 83 ].…”
Section: Transformation Of Microplastics In Inland Water Systemsmentioning
confidence: 99%
“…These phenomena are due to the fact that microplastics could transfer toxic substances and heavy metals as a carrier [ 94 , 95 ]. The toxins from the microplastics are released to the water systems via degradation consequently gaining entry into the food chains, which would also accumulate in organisms through the bioaccumulation process [ 83 ]. For instance, Wardrop et al [ 94 ] conducted a study to show that microbeads from personal care products have the potential to transfer adsorbed pollutants to the rainbow fish and then ingest them.…”
Section: Effects and Potential Risks Of Microplastics In Inland Water Systemsmentioning
confidence: 99%